The Moro Muslim Conflict in the Philippines: A Postcolonialism Perspective - Choiroh, Wahyuni Nuryatul (Faculty of Ushuluddin, Adab, and Humanities Universitas Islam Negeri Salatiga, 2023)
This article discusses the long and complex history of the Moro Nation, starting with the presence of Islam which flourished in the Southern Philippines. Then Spain came and the United States brought political and Christianization missions until the time of Philippine independence. The term